Ranking Fuzzy Numbers with Mean Value of Points and Comparative Reviews - Prasad, S.; Sinha, A. (Journal of Scientific Research, 2022)
Even though various ranking fuzzy numbers approaches have been presented so far, none of them can always provide satisfactory results in every situation. Some are counterintuitive, and some are inconsistent for the same circumstances. To overcome the issues mentioned above, we present a new technique for ranking fuzzy numbers using the mean value of the two points. The points are taken on the left and the right membership functions (reference functions) such that they divide the respective membership function in the same ratio . The proposed technique determines the order of the fuzzy numbers significantly. To use this technique, the membership functions need not be normal and linear.